Investigation of bioflocculant as renewable dewatering aid in sludge treatment - Jami, Mohammed Saedi; Mohd Arif, Aysha Ralliya; Abdulazeez, Qabas Marwan (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Sludge treatment is the most important and expensive step in water and wastewater treatment plants. Chemical conditioners such as polyaluminium chloride, aluminium sulfate, Fenton’s reagent, gypsum, and polyacrylamide can produce by-products, which cause health and environmental problems. Moringa oleifera (MO) seeds can be used as natural alternatives for chemical conditioners. The bioactive materials have to be extracted from MO seeds for better performance. Treatment methods of MO seeds investigated in this study were crude MO seeds, MO salt extraction by NaCl (1 M), and defatted MO seeds using hexane solvent. Synthetic sludge samples were prepared using kaolin suspension (5% w/v). The best extraction method was determined using settling velocity (Vs) and sludge volume index (SVI) as indicators. Results showed that salt extraction by NaCl gave the best results of 0.41 cm/min of settling velocity and 63.39 mg/L of SVI. The selected extraction method was optimized with respect to three process conditions: MO seeds concentration, mixing speed and contact time. The experiments were designed using 2 Level Factorial Design by Design-Expert software. The optimum process conditions were seeds concentration of 3250 mg/L, mixing speed of 100 rpm, and contact time of 17.5 min. MO seeds is consider a natural coagulant that can be used as main sludge conditioner.